Compact Real-Time Control System for Autonomous Vehicle - Choong, Florence Chiao Mei; Leong, Rong Fei (Journal of Advanced Industrial Technology and Application, 2022)
Due to global warming, there is an increase in the number of natural disasters occurring around the world. With more disasters happening, post disaster search and rescue personnel are putting their life on the line more often in scouting out the post disaster site and sending in first aid supplies while waiting for rescue vehicles like fire trucks and ambulance to arrive. In Malaysia alone, the use of compact autonomous landed vehicle (ALV) for this purpose is limited. There are many compact ALV that are being developed with microcontrollers and microprocessors such as Arduino and Raspberry Pi as the central control system, but they are fragile and can be damaged easily when used in harsh environments. In addition, multiple microcontrollers and microprocessors are needed for the ALV as parallel processing and limited gates are some of the common problems with microprocessors and microcontrollers. In this paper, a central control system using an FPGA is proposed together with the design of a prototype for the ALV. The ALV consists of three systems: Propulsion System, Sensor System, and Remote-Control System. These systems are integrated together with the Altera DE-115 board as the central control unit of the ALV. Verilog Hardware Description language (Verilog HDL) is used for designing the control system for the ALV. The proposed system is stable, low cost, allows parallel processing and the compact size of the ALV allows smooth manoeuvring through small areas of post disaster sites to scout out the area and send in first aid supplies to the victims.